Gross motor developmental delay and associated factors among under-five children attending public health facilities of Dessie city, Ethiopia - Kefale Mitiku; Tilaye Nega; Mastewal Arefaynie; Degalem Tilahun; Bereket Kefale; Yitayish Damtie; Bezawit Adane; Melaku Yalew (BMC, 2023)
Abstract Background Child psychomotor development and factors affecting it today is the subject of interest of many studies, in particular by the experts involved in the protection and improvement of children's health. There is limited evidence on developmental delay among under-five children in low-income countries like Ethiopia. The aim of this study was to assess gross motor developmental delay and associated factors among under-five children attending public health facilities of Dessie city, Ethiopia. Methods Facility based cross sectional study design was used among under-five children attending under-five OPD in public health facilities of Dessie town from July 1, 2020 to August 15, 2021. A total of, 417 under-five children were systematically selected based on their average number of clients in a month. A pretested structured questionnaire was used for data collection, and data was entered into Epi-data 3.1 version and it was exported to STATA version 14 for analysis. Binary logistic regression analysis was used to identify factors associated with the outcome variable. Odds ratio with 95% confidence interval was used to show the strength and direction of association respectively and P-value less than 0.05 is used to declare statistical significance. Results The overall proportion of gross motor developmental delay among under-five children attending health facilities of Dessie city, Ethiopia was 16.31%, 95% CI: (13.05, 20.19). Increased age of the child [AOR = 0.97, 95% CI: (0.96, 0.99)], increased gestational age during pregnancy [AOR = 0.47, 95% CI: (0.37, 0.65)], being male [AOR = 5.26, 95% CI: (1.76, 15.67)], having history of alcohol intake during pregnancy [AOR = 7.40, 95% CI: (2.36, 23.25)], taking iron during pregnancy [AOR = 0.04, 95% CI: (0.01, 0.15)], facing fetal and/or maternal complication [AOR = 4.98, 95% CI: (1.20, 20.62)], having instrumental delivery [AOR = 9.78, 95% CI: (2.48, 38.60)] were significantly associated with gross motor developmental delay. Conclusions The gross motor developmental delay among under-five children was higher as compared to other literatures. This study indicated that, age and sex of the child, iron and alcohol intake during pregnancy, gestational age, mode of delivery and any complication to her and or her neonate were independent variables which showed statistical significant association. The physicians should advise mothers to take iron-folic acid supplement properly and to avoid intake of alcohol during pregnancy. In addition, they should focus on those mothers who faced any complication to her and/or her neonate and better to discourage instrumental delivery unless there are no other options.